2014
DOI: 10.1080/00207543.2014.895063
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ISO 9000 implementation on flow management

Abstract: This study proposes an innovative flow management system that includes product (product and logistics) and process (human, information and decision) flow management. We identify three levels of ISO 9000 implementation (basic, advanced and supportive) as enablers, and operational performance as the outcome. The model was tested using the data-set collected from 133 ISO 9001 certified manufacturing companies in Australia. The results show that advanced implementation is positively related to both product and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 70 publications
(85 reference statements)
3
27
0
Order By: Relevance
“…The results is in line with previous findings obtained by Huo, Han and Prajogo (2014) on 121 factories that have received the ISO 9001 certificate in Australia and New Zealand where the organizational capability based on process flow management had a significant relationship with performance. In addition, Perez-Freije and Enkel (2007) in their research on the relationship between ability and process of innovation and control system or organizational performance, work structure, problem solving, working environment, compensation, and paradigm innovation showed that the process of innovation and control system or organizational performance is crucial in supporting the capability of a firm.…”
Section: Discussionsupporting
confidence: 82%
“…The results is in line with previous findings obtained by Huo, Han and Prajogo (2014) on 121 factories that have received the ISO 9001 certificate in Australia and New Zealand where the organizational capability based on process flow management had a significant relationship with performance. In addition, Perez-Freije and Enkel (2007) in their research on the relationship between ability and process of innovation and control system or organizational performance, work structure, problem solving, working environment, compensation, and paradigm innovation showed that the process of innovation and control system or organizational performance is crucial in supporting the capability of a firm.…”
Section: Discussionsupporting
confidence: 82%
“…• Training: companies looking for an effective ISO 9001 implementation arrange training programs for employees to improve their skill on quality standards, clarifying strategic directions and business goals (Huo et al, 2014). Training focused on quality and information programs is provided to ensure that there is a learning process in place for the success of the implementation.…”
Section: Iso 9001-critical Factors For Implementationmentioning
confidence: 99%
“…Factors that affect the success or failure of ISO 9001 implementation, and QMSs as a corollary have been studied in the literature. The focus on implementation factors is essential because the complete benefits of ISO 9001 can be experienced by an organization only after it has established the appropriate conditions for its implementation and sustenance (Huo et al, 2014). Prior work has focused on the identification of factors influencing effective implementation (Psomas et al, 2010), and evaluation of factors that impact organizations which plan to implement ISO 9001 (Augustyn and Pheby, 2000;Lin and Jang, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations